A 3rd generation web-based instructional tool for education and lifelong training. (1st January 2003) - Uskov, Vladimir
The state-of-the-art InterLabs Web-Based Instructional (WBI) tool has been designed, developed, and alpha-tested at the Department of Computer Science and Information Systems and the InterLabs Research Institute at Bradley University. It is based on active utilisation of innovative web-based software engineering, streaming multimedia, communication, teaching, learning and information technologies. It strongly supports the innovative learner-centred paradigm of learning/training. Multiple formative and summative evaluations by students, trainees, and instructors clearly demonstrate the advantages of online courseware developed and delivered by using the InterLabs WBI tool.